The rise of supermarkets and their development implications: International experience relevant for India - Reardon, Thomas; Gulati, Ashok (International Food Policy Research Institute, 2008)
The Indian Council for Research on International Economic Relations (ICRIER) was invited by the Indian Ministry of Commerce and Industry to conduct a study titled The Impact of Organized Retailing on the Unorganized Retail Sector." Because organized retail in India is still in its infancy, it was deemed critical to look at the experience of other countries, especially developing ones. Thus, ICRIER sought the assistance of Dr. Thomas Reardon and Dr. Ashok Gulati, co-directors of Markets in Asia, a joint program of the International Food Policy Research Institute (IFPRI) and Michigan State University. ICRIER asked Reardon and Gulati to help research and report on the international experiences in the growth and expansion of modern retailing in developed and developing countries and the implications for India. This report is a contribution to that effort. This paper focuses on the emergence of modern retailing with respect to food and what implications it can have for various stakeholders in the food supply chain. While we briefly review the US and European experience, we focus on the developing countries of Latin America and East Asia (including China), where the supermarket revolution started in the early to mid-1990s. We looked at the patterns of the diffusion process in modern retailing in terms of "waves" that go from country to country, and within a country from first-tier cities to second-tier and then third-tier cities, and from processed to semiprocessed to fresh products. We also treat the challenges and opportunities that modern retailing has posed for various stakeholders in the supply chains, especially for traditional retailers, farmers, and consumers. We also looked at several instances when governments helped small retailers or upgraded wetmarkets by (1) establishing affirmative action policies to strengthen their competitiveness so they could also participate effectively in the transition to modern retailing, and (2) providing compensation to help them change their lines. The paper concludes by surmising what lessons other countries' experiences in the supermarket revolution have for India which is on the threshold of a major structural change in retailing. The expectations and concerns are high. Accordingly, India must form its own model of retail development to meet its priorities, learn from challenges that others have faced, and successful examples of strategies for "competitiveness with inclusiveness" among traditional retailers, wholesaler, and farmers entering an era of rapid retail transformation and concomitant food system change.